Access to jobs and apartment rents. (July 2016) - Lin, Jen-Jia; Cheng, Yu-Chun
Abstract: This study empirically explores the relationship between access to jobs and apartment rents. Specifically, the research examines the following three hypotheses: job accessibility positively influences apartment rents, the effect of job accessibility on apartment rents varies by transportation mode, and the effect of job accessibility on apartment rents varies by rent level. To examine these hypotheses, this study applies gravity-type job accessibility indexes based on a study sample of 7077 observations in the Taipei Metropolitan Area, Taiwan, from the year 2009. The sample data are analyzed using linear and quantile regressions. The empirical evidence confirms the positive effect of job accessibility on apartment rents, and its variability depending on the transportation mode and rental level. The effect of job accessibility on apartment rent is significantly positive in the median or lower-rent-level sub-markets, but insignificantly negative in higher-rent-level sub-markets. Job accessibility by motorcycle and public transit has a higher positive influence on rent than accessibility by car. These findings provide new knowledge on the role of access to jobs in explaining apartment rents, and reveal a fresh policy direction on rental subsidy programs for lower-income workers living in cities. Highlights: Job accessibility positively influences apartment rents. The effect of job accessibility on apartment rents varies by transportation mode. The effect of job accessibility on apartment rents varies by rent level. The geographical accessibility and rent level submarket are worth considering in designing an active rent subsidy program.